Effectiveness of Using Animation Videos in Science Learning in Elementary Schools: A Systematic Literature Reviews - Putri, Siti Anisa; Rohmani; Apriza, Berta; Elizar (Indonesian Journal of Educational Research and Review, 2024)
Science learning in elementary schools plays a crucial role in fostering students' curiosity and interest in science, developing critical and logical thinking skills, and equipping students with scientific knowledge and practical skills applicable in daily life. This study aims to analyze the effectiveness of animated videos in enhancing science learning in elementary schools through a systematic literature review. Employing the Systematic Literature Review (SLR) method, data were sourced from Google Scholar, focusing on articles published between 2019 and 2023. The review was conducted in five stages. In the initial search using the keyword "use of animated videos," 1,280 documents were identified. Refining the search by limiting the publication years yielded 227 documents, while adding the keyword "science learning" identified 246 documents. Further narrowing with the keyword "primary school" produced 197 documents. Finally, the dataset was filtered based on alignment with the research theme. The findings reveal that animated videos are highly effective in enhancing science learning outcomes in elementary schools. These results emphasize the importance of integrating engaging instructional media, such as animated videos, to facilitate effective communication of science concepts. Educators are encouraged to incorporate such tools to create more interactive and impactful learning experiences in science education.